Biodiesel production from rubber seed oil using activated cement clinker as catalyst - Jolius, Gimbun; Shahid, Ali; Chitra Charan Suri Charan, Kanwal; Liyana Amer, Shah; Nurul Hidayah, Muhamad @ Ghazali; Chin, Kui Cheng; Said, Nurdin (Malaysian Technical Universities Network (MTUN), 2013)
Malaysian Technical Universities Conference on Engineering and Technology (MUCET) 2012 organised by technical universities under the Malaysian Technical Universities Network (MTUN), 20th - 21st November 2012 at Hotel Seri Malaysia, Kangar, Perlis, Malaysia.